Simon de Montfort and King Henry III: The First Revolution in English History, 1258–1265. Issue 12 (December 2013) - Ambler, Sophie T.
Abstract The reign of Henry III (1216–1272) was pivotal in English political history. It saw the entrenchment of Magna Carta, the growth of parliament and the widening of political society, as well as England's first revolution (1258–1265), led by Simon de Montfort, earl of Leicester. Montfort and his confederates seized the reins of government from Henry III and governed by a council in the king's name, in the most dramatic political upheaval before the 17th century civil war. Blessed with a rich collection of sources, historians over the past two decades have used the tools of military, biographical, intellectual and social history, as well as sociological approaches, to analyse these events. Their work has placed 13th century politics firmly within its own society and culture, throwing fresh light on Henry III, Simon de Montfort and the events of the first revolution in English history. © 2013 John Wiley & Sons Ltd